Non-adherence to psychotropic medication among adolescents: a systematic review of the literature = Nicht-Adhärenz bezüglich der Einnahme von Psychopharmaka bei Jugendlichen : ein systematischer Review - Häge, Alexander; Weymann, Lisa; Bliznak, Lucia; Märker, Viktoria; Mechler, Konstantin; Dittmann, Ralf (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2018)
Introduction: Whether patients take their medication as prescribed is of increasing importance in adolescent psychiatry since both the number of efficacious pharmaceutical treatments and the rate of prescriptions of psychotropic compounds are on the rise. Previous research showed high rates of medication nonadherence among both adolescents with medical disorders and adult patients with psychiatric disorders. Methods: The present review was performed according to PRISMA guidelines and evaluates existing scientific literature concerning adherence to psychotropic medication among adolescents. The goal was to determine rates of nonadherence in this age group as well as the factors associated with it. Therefore, we conducted a comprehensive literature search of PubMed from its inception until 15 September 2015 using the keywords “adherence,” “compliance,” “adolescent,” and “psychotropic medication.” Results: A total of 607 pertinent articles were collected and screened; 15 publications were selected for detailed review. The studies differed, among other things, regarding sample characteristics, medication type, and indications. Furthermore, the definitions of what constitutes nonadherence and the methods used to assess it varied widely. Nonadherence rates ranged from 6 % to 62 % (median 33 %). Conclusion: Nonadherence to psychotropic medication is a clinically relevant problem among adolescents. Because of the methodological heterogeneity across studies and partially contradictory results, no conclusions could be drawn concerning the influence of factors such as psychopathology, medication type, side effects, the effectiveness of treatment, or family-related factors. Well-designed long-term studies of large patient samples and a consensus regarding definitions are therefore warranted. Such research would facilitate the design of tailored strategies to improve adherence in these patients.
Gesehen am 04.09.2019
Article online: 07.12.2016